Murray Gell-Mann and the Physics of Quarks - Fritzsch, Harald (Classic Texts in the Sciences,, 2018)
Murray Gell-Mann, Physics Nobel Prize Laureate in 1969 is known for his theoretical work on elementary particle physics and the introduction of quarks and together with H. Fritzsch the "Quantum Chromodynamics". Based on four sections the Editor gives an overview on the work of Gell-Mann and his contributions to various aspects of the physics, related to quarks. His most important and influential papers were selected and reprinted so that the reader easily can check the original work of Gell-Mann.